Inhibitory effect of cinnamaldehyde on Fusarium solani and its application in postharvest preservation of sweet potato. (15th May 2023) - Pan, Chao; Yang, Kunlong; Erhunmwunsee, Famous; Li, Yong-Xin; Liu, Man; Pan, Shenyuan; Yang, Dongjing; Lu, Guoquan; Ma, Daifu; Tian, Jun
Graphical abstract: Highlights: Cinnamaldehyde (CA) exhibited antifungal effect on Fusarium solani . CA disrupted mitochondrial function and induced ROS accumulation. ROS peroxidized mitochondrial cardiolipin and initiated apoptosis in F. solani . CA holds promise as a preservative for postharvest storage of sweet potato. Abstract: Root rot caused by Fusarium solani is one of major postharvest diseases limiting sweet potato production. Antifungal effect and possible mode of action of cinnamaldehyde (CA) against F. solani were investigated. CA concentration of 0.075 g/L inhibited conidial viability of F. solani . CA vapor of 0.3 g/L in air completely controlled the F. solani development in sweet potatoes during storage for 10 days at 28 °C, and protected soluble sugar and starch in the flesh from depletion by the fungus. Further results demonstrated that CA induced reduction in mitochondrial membrane potential (Δψm ), ROS accumulation, and cell apoptosis characterized by DNA fragmentation in F. solani . Moreover, CA facilitated decomposition of mitochondria-specific cardiolipin (CL) into its catabolites by the catalytic action of phospholipases. Altogether, the results revealed a specific antifungal mechanism of CA against F. solani, and suggest that CA holds promise as a preservative for postharvest preservation of sweet potato.